Open source hardware and software platform for robotics and artificial intelligence applications. Issue 1 (February 2016) - Liang, S Ng; Tan, K O; Clement, T H Lai; Ng, S K; Mohammed, A H Ali; Mailah, Musa; Yussof, Wan Azhar; Hamedon, Zamzuri; Yussof, Zulkifli
Abstract: Recent developments in open source hardware and software platforms (Android, Arduino, Linux, OpenCV etc.) have enabled rapid development of previously expensive and sophisticated system within a lower budget and flatter learning curves for developers. Using these platform, we designed and developed a Java-based 3D robotic simulation system, with graph database, which is integrated in online and offline modes with an Android-Arduino based rubbish picking remote control car. The combination of the open source hardware and software system created a flexible and expandable platform for further developments in the future, both in the software and hardware areas, in particular in combination with graph database for artificial intelligence, as well as more sophisticated hardware, such as legged or humanoid robots.